Pemberdayaan Kader Kesehatan Desa Sempalwadak Kec. Bululawang, Kab. Malang Terkait Pembuatan Minyak Gosok dengan Kandungan Utama Minyak Peppermint Sebagai Pereda Nyeri - Sawu, Sirilus Deodatus; Hapysari, Yulinda Pristi Dwi (Universitas Pahlawan Tuanku Tambusai, 2026)
Peppermint oil has many health benefits, including relaxation, analgesic, anti-inflammatory, and used for nausea and vomiting. One of the benefits of peppermint oil as an analgesic has the potential to be developed into products such as massage oil to relieve pain. The purpose of the Community Service Program (PKM) activity is to increase knowledge and skills through counseling and training in making massage oil as a pain reliever with peppermint oil as the main ingredient. The participants of this activity were 18 health cadres from Sempalwadak Village, Bululawang District, Malang Regency. The method used was providing socialization through PowerPoint media and training in making peppermint oil massage. Evaluation of the measurement of understanding of community service participants by comparing the average pretest and posttest scores and evaluating the abilities of activity participants through a skills assessment sheet. The results of the participant knowledge evaluation showed that there was a success of the PkM activity as indicated by an increase in knowledge based on the average pretest-posttest value of 51.91% and the average skill score of participants was 3.78 with a very good category. This demonstrates that the information presented was well understood by the participants and indicates the success of the Community Service Program (PKM) activities.